Fourteen-year trends in sodium content of menu offerings at eight leading fast-food restaurants in the USA. Issue 8 (10th September 2013) - Rudelt, Amanda; French, Simone; Harnack, Lisa
Abstract Objective To examine changes in the Na content of lunch/dinner menu offerings at eight of the leading fast-food restaurants in the USA between 1997/1998 and 2009/2010. Design Menu offerings and nutrient composition information for the menu items were obtained from archival versions of the University of Minnesota Nutrition Coordinating Center (NCC) Food and Nutrient Database. Nutrient composition information for lunch/dinner menu items sold by the fast-food restaurants included in the present study was updated in the database biannually. Menus were analysed for changes in mean Na content of all menu offerings (except beverages) and specific categories of menu items among all restaurants and for each individual restaurant. Setting USA. Subjects Lunch/dinner food menu of eight leading US fast-food restaurants. Results Between 1997/1998 and 2009/2010 the mean Na content of menu offerings across the eight restaurants increased by 23·4 %. Examining specific food categories, mean Na content of entrées by increased 17·2 % and that of condiments increased by 26·1 %. Only side dishes showed a decrease of 6·6 %. None of the restaurants examined had a decrease in Na across the lunch/dinner menu offerings over the 14 years examined. Conclusions Results suggest that over the time period studied there has been no meaningful reduction in the Na content of lunch/dinner menu offerings at the leading fast-food restaurants examined in the present study.